Peran Guru M. Jeddawi “Harimau Jantan Kota Jambi” dalam Menegakkan Syari’at Islam pada Pertengahan Abad ke XX - Muthalib, A.; Putra, Edi Susrianto Indra; Khairuddin, Khairuddin (Al-Aulia: Jurnal Pendidikan dan Ilmu-Ilmu Keislaman, 2023)
In the past, one of the teachers (Kyai) named M. Jeddawi in Jambi was nicknamed by the community as the "Tiger of the City of Jambi," in addition to this nickname there was also another nickname for him, namely "Lion of Jambi" because his behavior bears a resemblance to Umar bin Khath-thab, as it is known that Umar bin Khath-thab was nicknamed the “Lion of the Desert” because of his brave attitude, that is what the “Male Tiger of Jambi City” did. In this research method we use the basis of historical methods, the theory is qualitative theory; the aim is to find out why the community gave the nickname “Male Tiger of Jambi City” to Kiyai M. Jeddawi? If observed, a role like that of Kiyai M. Jeddawi is very much needed, because his attitude is very helpful to the community, because of that the people in the city feel very lost. Hopefully someone like this character will emerge. We must admit, living in this era is much more difficult than conditions in the past.